Models of evaluation under ceteris imparibus: System dynamics and the example of emergency care. (29th August 2019) - McAvoy, Susan; Staib, Andrew; Birch, Stephen
Abstract: Traditional and current approaches to modelling the impacts of health care interventions have focused on detail complexity and been ceteris paribus dependent and thereby ignored the wider system impacts. In this study, we have demonstrated that system dynamics (SD) offers theoretical and practical advantages over conventional methodologies and the qualitative assessment tools that have informed the business of emergency care. We translate the key findings of qualitative research, existing literature reviews and studies of the use of simulation and economic evaluation models into a value proposition for using SD tools. We conclude that there is growing evidence of a strong value proposition for the use of SD tools to investigate interventions targeting improved emergency care access. SD models can incorporate dynamic and organizational complexity and fill a gap beyond the microscope of the conventional methodologies informing health care. This potential to strengthen health care systems warrants further investigation.